2017
DOI: 10.3389/fped.2017.00250
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Anti-N-Methyl-d-Aspartate Receptor Encephalitis: A Review with Pooled Analysis and Critical Care Emphasis

Abstract: PurposeAnti-N-methyl-d-aspartate receptor (NMDAR) encephalitis is being recognized with increasing frequency among children. Given the paucity of evidence to guide the critical care management of these complex patients, we provide a comprehensive review of the literature with pooled analysis of published case reports and case series.MethodsWe performed a comprehensive literature search using PubMed, Scopus, EMBASE, and Web of Science for relevant published studies. The literature search was conducted using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 83 publications
2
42
0
2
Order By: Relevance
“…Status epilepticus resulting from autoimmune encephalitis in the paediatric population is known. Anti-NMDA receptor antibodies are known to present with status epilepticus and dystonia in paediatric population 10. In our case, the autoimmune encephalitis panel was negative as well (table 1).…”
Section: Differential Diagnosissupporting
confidence: 51%
“…Status epilepticus resulting from autoimmune encephalitis in the paediatric population is known. Anti-NMDA receptor antibodies are known to present with status epilepticus and dystonia in paediatric population 10. In our case, the autoimmune encephalitis panel was negative as well (table 1).…”
Section: Differential Diagnosissupporting
confidence: 51%
“…6 For most cases of anti-NMDARe in children, the causative and triggering factors remain unclear. 7,8 Several infectious agents and vaccination may trigger anti-NMDARe. 5,9-12 Forty-three cases (including those of 31 children) of anti-NMDARe were found to be triggered by herpes simplex virus, as reported in a recent study.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Some microbial proteins induced by vaccination might cause autoimmune diseases because components of these proteins are similar to human proteins, 6 the patient with postvaccination anti-NMDARe identified in our review may further confirm this speculation; (2) JE vaccines have been reported to be linked to acute disseminated encephalomyelitis 15 ; therefore there is a chance that JEV may induce anit-NMDARe; (3) antigens released by viral neuronal lysis and inflammation have been hypothesized to lead to synaptic autoimmunity have been speculated, positive findings in the CSF but negative findings in the serum for anti-NMDAR were observed in half of the patients reviewed in our study. 7 Thus, the observation in favor of the hypothesis of neuronal destruction resulting from NMDAR exposure to central nervous system immunity which further leads to the development of anti-NMDAR.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Although cerebrospinal fluid (CSF) testing remains the gold standard (with sensitivity approaching 100%), a prior study evaluating large numbers of samples at a single center identified NMDAR IgG autoantibodies in the serum of more than 80% of affected patients. 7 These findings, if replicated in exemplar clinical environments, could be used to rationalize serum screening in patient populations and clinical settings where CSF collection is challenging, impractical, or inconvenient, including pediatric populations, 8 mental health settings, 9 and outpatient clinics.…”
Section: Introductionmentioning
confidence: 84%